0-72 Ay Aralığındaki Türk Çocuklarının Uyku Alışkanlıkları - Zeynep Çetin; İsmihan ARTAN; Özcan DOĞAN; Esra ACAR ŞENGÜL; Çiğdem AYDIN; Arzu YÜKSELEN (Hacettepe University, 2015)
Objectıve: The purpose of the study is to analyze children's sleeping habits. The sample included randomly selected mothers of 543 girls and 557 boys between the ages of 0-72 months. Materıals and Methods: Data collected by means of interviews with mothers and a short questionnaire was used during the interviews. Results: It was found out that there is a significant relationship between the mother's working condition and children's having a specific sleeping time and the lighting in the child's room. It was also realized that there is not a significant relationship between the mother's working conditions with the child's using a transitional object while falling to sleep, his sleeping with the parent, his waking up at night and coming to his parents' room. There was a significant relationship between the mother's education level and the specific time to sleep and the use of transitional object and lighting. Conclusıon: In conclusion, it could be speculated that mothers' working condition is an effective factor for their children's having specific time to sleep and need for lighting in their rooms. Mothers' educational level may be an effective factor for their children sleeping habits like having specific time to sleep, use of transitional objects..